ANALISIS PELAKSANAAN KEWENANGAN KEPALA DESA DALAM MEMBINA KEHIDUPAN MASYARAKAT DI DESA TANJUNG MEDANG KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Nurhidayanti Nurhidayanti; Dia Meirina Suri (UIR Press, 2018)
This research aims to see the implementation of the Authority of the Village Head in Fostering Community Life in Tanjung Medang Village, Rangsang District, Kepulauan Meranti Regency. The guidance indicators used include counseling, direction, and guidance. This type of research located in Tanjung Medang Village is a descriptive survey, which prioritizes questionnaires as a means of collecting data and data collected with this tool and then becomes the main raw material for analyzing empirical conditions from the objective existence of research objectives at the research site. There are two population groups and the sample in this study is the government of Tanjung Medang Village with 26 people and Tanjung Medang Village community with 74 people. The community in this case is the people who live in Tanjung Medang Village. The types and data collection techniques used consist of primary data collected using observation techniques. While the data analysis technique used is quantitative analysis. in the village of Tanjung Medang, the district of excitement in Meranti Island District, was in the fairly implemented category. Recommendations that need to be considered are mainly the level of community participation, by providing good socialization of activities and complementing infrastructure facilities for people's lives.